Teachers nicknames: Micro research in onomastics - Kostić-Stamenović Karolina; Dragumilo-Stefanović Marija (Visoka škola strukovnih studija za vaspitače, Kruševac, 2012)
This paper studies teacher's nicknames in the primary school Vuk Karadžić in Kruševac gathered through a survey for which the students were requested to state a teacher‟s nickname, its originator and motivations. By method of random sampling, 243 students were polled, and 217 nicknames were collected. This paper serves as yet another confirmation of the functionality of our language in various forms of expression. We observed that while most nicknames are invented by students, many are also thought up by teachers as well. Students readily adopted nicknames created by other teachers. We also observed that a teacher can have two, even three nicknames. This comes about when nicknames conceived by previous generations are passed on. We drew the conclusion that each new generation of students creates nicknames of their own, in addition to the 'old', previously existing ones. The nicknames reported reveal creativity, imagination and originality of students as well as their relation to their teachers, based on understanding and respect for teachers' personalities.